Shaping customer experiences through robot service quality: evidence from the Klang Valley hospitality industry / Anbarasan Rawitchandaran ... [et al.]. - Rawitchandaran, Anbarasan; Mohamad, Arifha; Abu Seman, Noor Aslinda; Mohd Angsor, Mohd Asmadi; Mohamad, Ashbie (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Customer satisfaction is one of the major concerns today. The COVID-19 epidemic has accelerated the use of robot servers in the hospitality sector in Malaysia grows increasingly as customers are more cautious about the dangers of direct physical contact. The study intends to identify the relationship between customer satisfaction and the implication of service quality on robots within the hospitality industry in Klang Valley. In addition, this study uses quantitative methods by distributing questionnaires to respondents. By using the SERVQUAL model, this study has outlined the five factors affecting the customer’s satisfaction which are tangibles, reliability, responsiveness, assurance, and empathy. Based on Krejcie & Morgan's sample size table, 384 respondents required for this study. Quantitative research methods were designed as the target respondents were customers from the Klang Valley area. The Statistical Packages for Social Science (SPSS) software is being utilized in this study to analyze the data obtained. The analysis consists of Pearson Correlation and Spearmen analysis. In line with the study’s objective, five main research questions are formed. The distribution of surveys helped this study accomplish its goals. Based on the statistical analysis, all service quality dimensions which are tangibility, reliability, responsiveness, assurance, and empathy of service robots have a significant effect on customer satisfaction in the hospitality industry of Klang Valley. As of that, governments can take this study as a fundamental to encourage and implement more of the service robots in the hospitality industry throughout Malaysia.